Strategy Analysis of the Implementation of the MBKM Curriculum at the University - Nofrizal Nofrizal; Arizal N; Idel Waldelmi; Aznuriyandi Aznuriyandi; Zulia Khairani; Undang Juju (AL-ISHLAH: Jurnal Pendidikan, 2022)
In 2021 until now, the government issued the Merdeka Learning Kampus Merdeka (MBKM) curriculum which requires universities to implement, but it takes the right strategy, the purpose of this research is to find the strategic position of the Faculty of Economics at a private university in Riau to implement the MBKM curriculum, identify strengths, weaknesses, opportunities and threats and Develop alternative strategic options for the implementation of the MBKM Curriculum. The research method uses qualitative. The object of this research is the Faculty of Economics which has 2 study programs, namely Accounting and Management. Data sources are primary and secondary data. Data collection techniques using observation techniques, interviews and questionnaires. The number of samples in this study were 8 people using a sampling technique, namely saturated/census samples where the respondents were those who occupied strategic positions in decision making, expert judgment and stakeholders from faculties and universities. Data analysis used EFAS Matrix, IFAS Matrix, IE Matrix, SWOT-8K Matrix and TWOS Matrix. The results of the study indicate that the external and internal environmental conditions of the economics faculty show conditions that fall into the moderate/good category, which means the Faculty of Economics is able to implement this MBKM program. Meanwhile, the results of the IE Matrix value show that the position / quadrant of the Faculty of Economics is in the V Bold and maintain position (maintain and maintain) Market penetration and product development, while the analysis using the SWOT-8K matrix shows the quadrant position is in Diversification IV.